Caracterización físico-químico de la harina a partir de semilla de mora (Rubus glaucus), y su utilización en la elaboración de alimentos enriquecidos - Cedeño García, María Enriqueta (2015)
The present study physicist - chemist of the flour claims the Characterization from seed of default (Rubus glaucus), and his utilization in the production of enriched food. For this, they were evaluated the times and temperatures of dried of the seed of default (Rubus glaucus), the first treatment was left 74 hours to 65°C and the second one 94 hours to 40°C in addition, the addition of acid was evaluated ascórbico in the flour, to the first treatment (65 °C) it one was divided in two equal parts by acid and other one without acid of the same form of I realize with the second treatment (40 °C) remaining like proved 4 treatments.To the flour there was realized analysis of Dampness, Ash, Protein, and dietetic Fiber, to determine if there exists significant difference between 4 treatments, every analysis was done by duplicate to endorse the obtained results. The aims of study in the production of enriched cookies were to determine the suitable percentage of flour of seed of default, one used two different percentages in the production of the same ones, (5 % and 10 %) and there was valued the addition of qualit fat (Ac. of sunflower, olive, and sacha inchi), remaining like proved 6 treatments. There was realized analysis of Dampness, Ash, pH and Protein, to the Cookies to determine one exists significant difference between the factors of study.In the statistical analysis one used two designs factoriales of A*B, with duplicate. For the analysis of information there used the statistical package StatsGraphics Centurión of the University of Massachusetts, for the separation of averages of the levels of the treatments there was in use the test of TUKEY's significance (p> 0.05). In the obtaining of the flour in the factor To significant difference decided in: